2021
DOI: 10.1186/s40545-021-00307-w
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers and facilitators to uptake of non-traditional roles by pharmacists in Saudi Arabia and implications for COVID-19 pandemic and beyond: a qualitative study using Theoretical Domain Framework

Abstract: Background The COVID-19 pandemic has further strengthened the need for pharmacists to uptake non-traditional roles. Pharmacy practice in Saudi Arabia is emerging in recent years with greater policy emphasis on pharmacists taking new clinical roles. This study aimed to explore the experiences, perceptions and barriers of Saudi pharmacists about their uptake of non-traditional roles using Theoretical Domains Framework (TDF). Methods A qualitative sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 52 publications
3
31
0
Order By: Relevance
“…These findings were line with previous study. 56 The CPs’ lack of knowledge about their roles and skills needed during the COVID‐19 pandemic were also indicated as barriers. Behaviour change strategies could be used to develop and implement interventions targeting these barriers, which were identified using the TDF.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were line with previous study. 56 The CPs’ lack of knowledge about their roles and skills needed during the COVID‐19 pandemic were also indicated as barriers. Behaviour change strategies could be used to develop and implement interventions targeting these barriers, which were identified using the TDF.…”
Section: Discussionmentioning
confidence: 99%
“…The Saudi Arabian qualitative study showed that the acceptance of pharmacists' non-traditional roles was generally positive at the policy level ( 18 ). However, the acceptance of these non-traditional roles by other healthcare professionals and patients required further education.…”
Section: Discussionmentioning
confidence: 99%
“…These studies describe pharmacists' clinical activities in pharmacotherapy consultation and drug therapy monitoring, chronic disease management, and drug supply guarantee in public health crises. Researchers from Saudi Arabia explored pharmacists' non-traditional roles, and barriers and facilitators in performing these roles during the COVID-19 epidemic ( 18 ). One study examined strategies to strengthen the role of community pharmacists in public health ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines from the China National Health Commission made no mention of pharmacists getting involved in the treatment plan. Clinical pharmacists have not fully exerted their professional [15] values due to the following factors of 1) the demand for physicians and nurses in a public health crisis is generally far more signi cant than pharmacists [16] and 2) the shortage of medical resources [17]. During the outbreak, resources such as masks and protective clothing were in short supply [18][19][20] and must be provided to doctors and nurses [21].…”
Section: Discussionmentioning
confidence: 99%